2021
DOI: 10.3389/fimmu.2021.709229
|View full text |Cite
|
Sign up to set email alerts
|

IL-27 Mediates Pro-Inflammatory Effects via the ERK Signaling Pathway During Preterm Labor

Abstract: Preterm labor (PTL) is a multifactorial syndrome that results in birth prior to 37 weeks of gestation. However, the specific molecular mechanisms underlying this condition have yet to be elucidated. Previous research demonstrated that the abnormal expression of IL-27, and its receptors, played a role in the pathophysiology of preterm labor. In the present study, we established a Lipopolysaccharide (LPS)-stimulated, infection-induced, preterm mouse model based on wild-type C57BL/6 mice and WSX-1-/-C57BL/6 mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…miR-132-3p was also shown to be involved in the development of preeclampsia by promoting trophoblast cells viability and invasiveness, and inhibiting apoptosis via targeting DAPK-1 [21]. There is growing body of evidence indicating that the activation of ERK, p38, JNK, NF-κB, and STAT3 signaling pathways participate in the process of initiation parturition and preterm labor, particularly in inflammatory and hormonal aspects [32][33][34][35]. The actions of miR-132-3p are closely related to these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…miR-132-3p was also shown to be involved in the development of preeclampsia by promoting trophoblast cells viability and invasiveness, and inhibiting apoptosis via targeting DAPK-1 [21]. There is growing body of evidence indicating that the activation of ERK, p38, JNK, NF-κB, and STAT3 signaling pathways participate in the process of initiation parturition and preterm labor, particularly in inflammatory and hormonal aspects [32][33][34][35]. The actions of miR-132-3p are closely related to these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…LPS is widely used to establish the cell model of PTB. 19,23,24 We then investigated the potential effect of miR-26a-5p on TRPC3 expression in a cell model of PTB. The results demonstrated that the expression of TRPC3 was remarkably upregulated in LPS-stimulated cells (a cell model of PTB) compared to the control cells.…”
Section: Overexpression Of Mir-26a-5p Decreases Trpc3 Levels In Lps-s...mentioning
confidence: 99%
“…22 LPS is widely used to establish an in vitro model of PTB. 19,23,24 In our study, we investigated the role of miR-26a-5p/TRPC3 axis in PTB using this model.…”
mentioning
confidence: 99%
“…They have been used to validate some compounds potentially preventing preterm delivery, such as naloxone, progesterone or corticoids (Romero et al, 2006;Arenas-Hernandez et al, 2019;Green and Arck, 2020;Galaz et al, 2021;Ginsberg et al, 2021). Lipopolysaccharide (LPS) stimulated infection is one of the most popular models to study inflammatory preterm birth, probably because of its low-cost and effectivity (Huang et al, 2021). Within this model, several inflammatory pathways and features have been profoundly studied during preterm labor, such as the implication of Interleukin-27 (IL-27) in the activation of extracellular signal-regulated kinases (ERK) pathway, which ultimately origins preterm labor (Huang et al, 2021).…”
Section: Lessons From Murine Models: Inflammatory Vs Non-inflammatory...mentioning
confidence: 99%
“…Lipopolysaccharide (LPS) stimulated infection is one of the most popular models to study inflammatory preterm birth, probably because of its low-cost and effectivity (Huang et al, 2021). Within this model, several inflammatory pathways and features have been profoundly studied during preterm labor, such as the implication of Interleukin-27 (IL-27) in the activation of extracellular signal-regulated kinases (ERK) pathway, which ultimately origins preterm labor (Huang et al, 2021). In this model, interventions with probiotics, such as Lentilactobacillus kefiri (Lk48), can impair the inflammatory process and diminish the rate of neonatal death (Ventimiglia et al, 2021).…”
Section: Lessons From Murine Models: Inflammatory Vs Non-inflammatory...mentioning
confidence: 99%